Rewrite the equation 11 x - 5 x 2 + 7 = 6 in standard form and identify a, b, and c

Answers

Answer 1
Answer:

Answer:

5x^2 - 11x = 1

This is now in standard form, where a = 5, b = -11, and c = 1.

Step-by-step explanation:

To rewrite the equation 11x - 5x^2 + 7 = 6 in standard form, we need to rearrange the terms so that the polynomial is in descending order of degree, with no missing terms. The standard form of a quadratic equation is ax^2 + bx + c = 0, where a, b, and c are constants.

So, let's start by moving the constant term to the right-hand side of the equation:

11x - 5x^2 = 6 - 7

11x - 5x^2 = -1

Next, we can multiply both sides of the equation by -1 to make the coefficient of the x^2 term positive:

5x^2 - 11x = 1

This is now in standard form, where a = 5, b = -11, and c = 1.


Related Questions

Miranda wants to give her 14-year-old daughter $20,000 when she turns 18. How much does she need to put in the bank now if the interest rate is 10 percent per year?
Please help! will give brainly
The following function represents the production cost f(x), in dollars, for x number of units produced by company 1:f(x) = 0.25x2 − 8x + 600The following table represents the production cost g(x), in dollars, for x number of units produced by company 2:x g(x)6 862.28 856.810 85512 856.814 862.2Based on the given information, the minimum production cost for company :blank:is greater.[Put 1 or 2 in the blank space]
Find the solution to the following equation by transforming it into a perfect square trinomial.x2 – 12x = 13        {46, 55}        {–1, 13}        {–15, 27}        {–21, 33}
A=1300e^(.043*5)=$1611.82Where do they get the value for e? (2.718281828459)

Explain how to find the simplest form of 100/1000

Answers

what you would do is you would take it and divide it.OK.and your answer would be 1/10.
Here is a trick my math teacher taught me for multiples of ten while doing fractions:

How many zeroes are in the numerator? (In your case, two.)
How many zeroes in the denominator? (In your case, three.)
In your case, you have two zeroes in the numerator. Now you would take away two zeroes in the denominator. So you would get now, 1/10. I hope this helped. 

What units could you use to measure the height of a hexagonal prism?cm
cm 2
cm 3
cm 4

Answers

Answer: A. cm

Step-by-step explanation:  The formula for the volume of a hexagonal prism is, volume = [(3√3)/2]a2h cubic units where a is the base length and h is the height of the prism. We can also use the other formula V = 3abh, where a = apothem length, b = length of a side of the base, and h = height of the prism.

no aswer for that question

Frank has enough paint to cover 500 square inches. He paints a wooden cube that has 9-inch square faces. How much paint does Frank have left?

Answers

Answer:

there are 6 square faces in a cube

surface 1 side: 9²=81inch²

1cube surface: 81*6=486inches²

he uses 486inch² of paint for the cube

Amount of paint remaining = 500 square inches - 486 square inches = 14 square inches

Step-by-step explanation:

Olivia and her friends went to a movie at 1:50 P.M. The movie ended at 4:10 P.M. How long was the movie?

Answers

Answer: The movie was 2 hours and 20 minutes long.

Step-by-step explanation:

basic adding + subtracting

Lim[(sqrt(cos(2x))-cubicrootof(cos(x))]/arctg(x^2) when x->0

Answers

\lim\limits_(x\to0)\frac{√(cos2x)-\sqrt[3]{cosx}}{arctanx^2}=\left[(0)/(0)\right]\n\nDe\ L'Hospital's\ rule:\n\n\lim\limits_(x\to0)\frac{√(cos2x)-\sqrt[3]{cosx}}{arctanx^2}=\lim\limits_(x\to0)\frac{(√(cos2x)-\sqrt[3]{cosx})'}{(arctanx^2)'}=(*)\n-------------------------------\n(√(cos2x)-\sqrt[3]{cosx})'=(-sin2x)/(√(cos2x))-\frac{-sinx}{3\sqrt[3]{cos^2x}}=\frac{-2sinxcosx\cdot3\sqrt[3]{cos^2x}+sinx√(cos2x)}{3√(cos2x)\cdot\sqrt[3]{cos^2x}}\n\n(arctanx^2)'=(2x)/(x^2+1)

-------------------------------\n(*)=\lim\limits_(x\to0)\frac{-6sinxcosx\sqrt[3]{cos^2x}+sinx√(cos2x)}{3\sqrt[3]{cos^2x}\cdot√(cos2x)}:(2x)/(x^4+1)\n\n=\lim\limits_(x\to0)\frac{-sinx(6cosx\sqrt[3]{cos^2x}-√(cos2x))}{3\sqrt[3]{cos^2x}\cdot√(cos2x)}\cdot(x^4+1)/(2x)\n\n=\lim\limits_(x\to0)(-sinx)/(x)\cdot\frac{(6cosx\sqrt[3]{cos^2x}-√(cos2x))(x^4+1)}{6}=-1\cdot\frac{(6\cdot1\sqrt[3]{1^2}-\sqrt1)(0+1)}{6}\n\n=-1\cdot(5)/(6)=-(5)/(6)

Solve the inequality 5x-7<2x -1

Answers

You have to move the x's to one side so
5x-2x<-1+7
3x<6
Then you get x alone so you divide both sides by 3
X<2
You switch the sign
X>2
To solve the inequality, we have to isolate x. Here's how:

5x-7\ \textless \ 2x-1 \n (5x-7)+7\ \textless \ (2x-1)+7 \n 5x\ \textless \ 2x+6 \n (5x)-2x\ \textless \ (2x+6)-2x \n 3x\ \textless \ 6 \n (3x)/(3) \ \textless \ (6)/(3) \n x\ \textless \ 2

Your answer is x<2.

Hope this helps!